CAN ATHEROSCLEROSIS BE ONE OF THE CAUSES OF ANTERIOR SPINAL ARTERY THROMBOSIS? - Almadani, Abubaker; Malik, Yasir Mehmood; Dar, Javeed Ahmed (Journal of Ayub Medical College Abbottabad, 2012)
A middle aged diabetic, hypertensive, dyslipidemic, heavy alcohol consumer man came with sudden onset upper back pain and quadriparesis. Examination showed upper motor type quadriparesis with sensation of pain loss up to level of C7 and totally spared proprioception. MRI spine showed features suggestive of anterior spinal artery stroke. Can atherosclerosis be a causative factor for spinal stroke? Keywords: spinal stroke, spinal cord ischemia, atherosclerosis, quadriparesis